2016
DOI: 10.1152/ajpcell.00293.2015
|View full text |Cite
|
Sign up to set email alerts
|

Iroquois homeobox transcription factor (Irx5) promotes G1/S-phase transition in vascular smooth muscle cells by CDK2-dependent activation

Abstract: The Iroquois homeobox (Irx5) gene is essential in embryonic development and cardiac electrophysiology. Although recent studies have reported that IRX5 protein is involved in regulation of the cell cycle and apoptosis in prostate cancer cells, little is known about the role of IRX5 in the adult vasculature. Here we report novel observations on the role of IRX5 in adult vascular smooth muscle cells (VSMCs) during proliferation in vitro and in vivo. Comparative studies using primary human endothelial cells, VSMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…As for a FOSB down-regulation effect, further investigation will be needed to understand how the down regulation of FOSB plays a role in cancer cell development. This hypothesis is further supported by the results of others showing that TEAD4 [27][28][29][30], HMGA1 [31][32][33][34], and IRX5 [35][36][37] are related to cell proliferation, cell cycle mechanisms, and cancer development. Other than these genes, some genes in our intersection sub-network are also involved in cell proliferation mechanisms, such as FOXM1 [38], MYBL2 [39], and the SOX transcription family [40,41].…”
Section: Pathway Related To Cancer Developmentsupporting
confidence: 72%
“…As for a FOSB down-regulation effect, further investigation will be needed to understand how the down regulation of FOSB plays a role in cancer cell development. This hypothesis is further supported by the results of others showing that TEAD4 [27][28][29][30], HMGA1 [31][32][33][34], and IRX5 [35][36][37] are related to cell proliferation, cell cycle mechanisms, and cancer development. Other than these genes, some genes in our intersection sub-network are also involved in cell proliferation mechanisms, such as FOXM1 [38], MYBL2 [39], and the SOX transcription family [40,41].…”
Section: Pathway Related To Cancer Developmentsupporting
confidence: 72%
“…Given the relationship between IRX5 and overall survival in patients with CRC, we believe that IRX5 plays an important role in the later stages of the disease. Taking into consideration the previous studies have shown that IRX5 participates in cell cycle and tumorigenesis . It appears that IRX5 is involved in the entire process of CRC.…”
Section: Discussionmentioning
confidence: 90%
“…Taking into consideration the previous studies have shown that IRX5 participates in cell cycle and tumorigenesis. 23,24 It appears that IRX5 is involved in the entire process of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-binding motif with a length of 60 amino acids called the homeodomain. 3 In mammals, we divided six genes of the Iroquois into two homologous clusters, IRXA (IRX1, IRX4, and IRX5) and IRXB (IRX2, IRX3, and IRX6) which had the position on chromosome 8 and chromosome 16, respectively. 4 In previous research, Iroquois proteins have a vital function in early embryonic patterning, cell-type specification as well as tumorigenesis, either as activators or repressors.…”
Section: Introductionmentioning
confidence: 99%